Association between high body mass index and prognosis of patients with early-stage breast cancer: A systematic review and meta-analysis - Li, Zhoujuan; Shen, Guoshuang; Shi, Mingqiang; Zheng, Yonghui; Guan, Yumei; Xin, Yuanfang; Wang, Miaozhou; Zhao, Fuxing; Ren, Dengfeng; Zhao, Jiuda (Cancer pathogenesis and therapy, 2023)
A high body mass index (BMI) can indicate overweight or obesity and is a crucial risk factor for breast cancer survivors. However, the association between high BMI and prognosis in early-stage breast cancer (EBC) remains unclear. We aimed to assess the effects of high BMI on the prognosis of patients with EBC. The PubMed, Embase, and Cochrane Library databases and proceedings of major oncological conferences related to the effects of BMI on the prognosis of breast cancer were searched up to November 2021. Fixed- and random-effects models were used for meta-analyses. Pooled hazard ratios (HRs) and 95% confidence intervals (CIs) for disease-free survival (DFS) and overall survival (OS) were extracted from the included literature. Twenty retrospective cohort studies with 33,836 patients with EBC were included. Overweight patients had worse DFS (HR: 1.16, 95% CI: 1.05–1.27, P = 0.002) and OS (HR: 1.20; 95% CI: 1.09–1.33, P < 0.001). Obesity also had adverse effects on DFS (HR: 1.17, 95% CI: 1.07–1.29, P = 0.001) and OS (HR: 1.30, 95% CI: 1.17–1.45, P < 0.001). Likewise, patients with high BMI had worse DFS (HR: 1.16, 95% CI: 1.08–1.26, P < 0.001) and OS (HR: 1.25, 95% CI: 1.14–1.39, P < 0.001). In subgroup analyses, overweight had adverse effects on DFS (HR: 1.11, 95% CI: 1.04–1.18, P = 0.001) and OS (HR: 1.18, 95% CI: 1.11–1.26, P < 0.001) in multivariate analyses, whereas the relationship that overweight had negative effects on DFS (HR: 1.21, 95% CI: 0.99–1.48, P = 0.058) and OS (HR: 1.39, 95% CI: 0.92–2.10, P = 0.123) was not statistically significant in univariate analysis. By contrast, obesity had adverse effects on DFS (HR: 1.21, 95% CI: 1.06–1.38, P = 0.004 and HR: 1.14, 95% CI: 1.08–1.22, P < 0.001) and OS (HR: 1.33, 95% CI: 1.15–1.54, P < 0.001 and HR: 1.23, 95% CI: 1.15–1.31, P < 0.001) in univariate and multivariate analyses, respectively. Compared with normal weight, increased body weight (overweight, obesity, and high BMI) led to worse DFS and OS in patients with EBC. Once validated, these results should be considered in the development of prevention programs. [Display omitted] •The impact of high body mass index (BMI) on the prognosis of patients with early-stage breast cancer (EBC) was examined.•A meta-analysis of 20 studies with 33,836 patients with EBC was carried out.•High BMI (overweight or obesity) had adverse effects on disease-free survival and overall survival in patients with EBC.•Clinicians should recommend regular physical activity and weight reduction to patients with EBC. This may prolong survival and improve prognosis and quality of life in patients with EBC.